2014
DOI: 10.1021/ie402547m
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Study the Synergistic Inhibition Effect of Cationic and Anionic Surfactants on the Corrosion of Mild Steel in HCl Solution

Abstract: The corrosion inhibition characteristics of cation-rich and anion-rich catanionic mixtures of cetyltrimethyl ammonium bromide (CTAB) and sodium dodecyl sulfate (SDS) as corrosion inhibitor for mild steel (MS) in aqueous solution of 2 M HCl were investigated. The interaction between the two surfactants in the solid−liquid interface was analyzed on the basis of regular solution theory for the first time. Mixed surfactants showed good inhibition properties due to strong adsorption on the surface and formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…34,35 Similar results were achieved in previous works. 36,37 Moreover, the % IE of these ILs within the same concentration follows the order IL 2 > IL 1 , this performance may be referred to the adsorption capability of the ILs studied, which mainly attributing to the increasing in adsorption density at the metal surface with rising of the molecular size of ILs. Hence, the variation in the anionic parts of IL 1 and IL 2 is responsible for the different size changes and different performance of the ILs in the inhibition efficiency.…”
Section: Weight Loss Methodsmentioning
confidence: 95%
“…34,35 Similar results were achieved in previous works. 36,37 Moreover, the % IE of these ILs within the same concentration follows the order IL 2 > IL 1 , this performance may be referred to the adsorption capability of the ILs studied, which mainly attributing to the increasing in adsorption density at the metal surface with rising of the molecular size of ILs. Hence, the variation in the anionic parts of IL 1 and IL 2 is responsible for the different size changes and different performance of the ILs in the inhibition efficiency.…”
Section: Weight Loss Methodsmentioning
confidence: 95%
“…By closer observation of polarization curves, it illustrates that the appearance of the polarization curves remains same in the presence of different concentrations of PCN. However, the curves were shifted steadily towards lower current density in the presence of the PCN, and it can be obviously concluded that the addition of PCN retard the corrosion process and caused the small changes in the E corr value, which suggests that the PCN acts as mixed-type inhibitor [23]. Potentiodynamic polarization parameters such as corrosion potential (E corr ), corrosion current density (i corr ), anodic slope (␤a), cathodic slope (␤c), and corrosion rate (CR) were obtained from the Tafel plot and are reported in Table 1.…”
Section: Corrosion Behavior Of Synthesized Pani/ceo 2 Nanocompositementioning
confidence: 95%
“…15 The calculated values of DG 0 ads is À31.36 kJ mol À1 , which means that the study of the interaction between solution and Q235 carbon steel surface suggests both physisorption and chemisorption. 41,42…”
Section: Adsorption Isothermmentioning
confidence: 99%